Implementasi Benchmarking OSIS MAS Al-Anwar Pontianak: Analisis Studi Kasus Dan Efektifitasnya - Faisol; Abdul Wahab (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This research aims to examine the implementation of benchmarking in the management of the Student Organization Intra School (OSIS) at MAS Al-Anwar Pontianak and analyze its effectiveness in improving the quality of the student organization. The approach used is qualitative with a case study method. Data collection techniques include observation, in-depth interviews, literature study, and surveys. Data analysis was conducted using the Miles and Huberman model, which includes four stages: data collection, data reduction, data presentation, and conclusion drawing. The research results show that benchmarking against OSIS MAN 1 Pontianak has made a positive contribution to the development of work programs, leadership training, documentation digitization, and strengthening external cooperation. The implementation of benchmarking was carried out through five stages: planning, analysis, integration, implementation, and operational maturity. However, the effectiveness of the implementation still faces several challenges such as the lack of active member participation, weak internal communication, and limited facilities. Nevertheless, benchmarking has proven to be a strategy capable of driving organizational culture transformation and the continuous improvement of OSIS quality. This study recommends strengthening mentoring, enhancing the competence of the management, and conducting regular evaluations to achieve maximum organizational success.